2018
DOI: 10.3390/s18061748
|View full text |Cite
|
Sign up to set email alerts
|

Stand-Alone Wearable System for Ubiquitous Real-Time Monitoring of Muscle Activation Potentials

Abstract: Wearable technology is attracting most attention in healthcare for the acquisition of physiological signals. We propose a stand-alone wearable surface ElectroMyoGraphy (sEMG) system for monitoring the muscle activity in real time. With respect to other wearable sEMG devices, the proposed system includes circuits for detecting the muscle activation potentials and it embeds the complete real-time data processing, without using any external device. The system is optimized with respect to power consumption, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…An EMG sensor attached to muscles around eyelid region captured the duration of eyelid closure as an indicator of drowsiness (Artanto et al, 2017 ). Another recent study has proposed a system that can detect real-time changes in EMG (Mazzetta et al, 2018 ). Further research is needed to validate EMG's applicability in real-world settings.…”
Section: Psychophysiological Measures To Assess Cognitive Statesmentioning
confidence: 99%
“…An EMG sensor attached to muscles around eyelid region captured the duration of eyelid closure as an indicator of drowsiness (Artanto et al, 2017 ). Another recent study has proposed a system that can detect real-time changes in EMG (Mazzetta et al, 2018 ). Further research is needed to validate EMG's applicability in real-world settings.…”
Section: Psychophysiological Measures To Assess Cognitive Statesmentioning
confidence: 99%
“…Moreover, an accurate skin preparation helps reduce certain components of artifacts [ 56 ]. In a previous work, we already demonstrated that the muscle activity type in healthy subjects can be identified with a wearable system studying the sign of the LP filtered sEMG signal below 10 Hz [ 58 ]. In particular, the positive sign was related to contraction and the negative sign to stretching.…”
Section: Analysis Of Antagonist Muscles Activation Patterns Duringmentioning
confidence: 99%
“…The addition of quantitative measures in assessing dystonia in different body segments may be instrumental for making a more accurate diagnosis. In this regards, technological innovations, like video-analysis or the use of wearable sensors may be exploited for a quantitative analysis of dystonia (16,17). In our sample, patients with focal neck onset with no spread showed shorter disease duration compared to the other subgroups, suggesting that in patients with CD, spread could appear later during the course of dystonia.…”
Section: Discussionmentioning
confidence: 83%
“…The addition of quantitative measures in assessing dystonia in different body segments may be instrumental for making a more accurate diagnosis. In this regards, technological innovations, like video-analysis or the use of wearable sensors may be exploited for a quantitative analysis of dystonia ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%